Analisis Pengaruh Komitmen Afektif Dan Kepemimpinan Trilogi Terhadap Organizational Citizenship Behavior Melalui Motivasi Intrinsik Sebagai Variabel Intervening (Studi Kasus Pada Anggota Ditreskrimum POLDA DIY) - Putra Hana, Yogananda Enggara; Lukitaningsih, Ambar; Kirana, Kusuma Chandra (Universitas Muhammadiyah Metro, 2023)
This study aims to analyze the relationship between Affective Commitment and LeadershipTrilogy on Organizational Citizenship Behavior through Intrinsic Motivation as an interveningvariable for members of the Ditreskrimun POLDA DIY. This research method uses quantitativedescriptive by using primary data obtained from the distribution of questionnaires. In this studyusing a simple random sampling technique, namely the sample is taken at random and eachmember of the sample has the same opportunity to be sampled. The number of samples taken in this study were 78 questionnaires. Data analysis using SPSS and Smart PLS. The results showed that affective commitment has a positive and significant effect on intrinsic motivation with a significance level of 0.003 <0.05, so my hypothesis is accepted. The trilogy leadership has a positive and significant effect on intrinsic motivation with a significance level of 0.003 <0.05, so hypothesis II is accepted. Affective commitment has no positive and significant effect on OCB with a significance level of 0.407 > 0.05, so hypothesis III is rejected. The trilogy leadership has a positive and significant effect on OCB with a significance level of 0.00 < 0.05, so hypothesis IV is accepted. Intrinsic motivation has a positive and significant effect on OCB with a significance level of 0.0014 <0.05 (p<0.05), so hypothesis V is accepted. Affective commitment to OCB with intrinsic motivation as an intervening variable with a significance level of 0.003 < 0.05 (p <0.05), then hypothesis VI is accepted. The trilogy of leadership towards OCB with intrinsic motivation as an intervening variable with a significance level of 0.000 < 0.05 (p <0.05) means that hypothesis VII is accepted. Keywords: Affective Commitment, Leadership Trilogy, Organizational Citizenship Behavior (OCB), Intrinsic Motivation